2018
DOI: 10.1161/circgen.118.002293
|View full text |Cite
|
Sign up to set email alerts
|

Nocturnal Atrial Fibrillation Caused by Mutation in KCND2 , Encoding Pore-Forming (α) Subunit of the Cardiac Kv4.2 Potassium Channel

Abstract: Background: Paroxysmal atrial fibrillation (AF) can be caused by gain-of-function mutations in genes, encoding the cardiac potassium channel subunits KCNJ2 , KCNE1 , and KCNH2 that mediate the repolarizing potassium currents I k1 , I ks , and I kr , respectively. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 50 publications
0
20
0
Order By: Relevance
“…1 D). Gain-of-function variants in KCND2 have been implicated in nocturnal atrial fibrillation [ 37 ]. The nocturnal occurrence of symptoms was attributed to the circadian variation of Kv4.2 in murine hearts with a substantial 2-fold change in expression between night and day [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…1 D). Gain-of-function variants in KCND2 have been implicated in nocturnal atrial fibrillation [ 37 ]. The nocturnal occurrence of symptoms was attributed to the circadian variation of Kv4.2 in murine hearts with a substantial 2-fold change in expression between night and day [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…We analyzed data from patients suffering from rare diseases that manifest in specific tissues. Patients were previously genetically diagnosed via exome sequencing and subsequent analysis as previously described 7073 . The data per patient was de-identified, and variants were filtered as follows: kept variants with call quality at least 20.0 in cases or at least 20.0 in controls AND outside top 5.0% most exonically variable 100base windows in healthy public genomes (1000 genomes). excluded variants that were observed with an allele frequency greater than or equal to 0.5% of the genomes in the 1000 genomes project OR greater than or equal to 0.5% of the NHLBI ESP exomes (All); or greater than or equal to 0.5% of the ExAC Frequency; or greater than or equal to 0.5% of the gnomAD Frequency; or filter variants unless established pathogenic common variant. kept variants (up to 20 bases into intron) that were experimentally observed to be associated with a phenotype: Pathogenic, possibly Pathogenic or disease-associated according to HGMD; or clinically relevant variants from CentoMD; or frameshift, in-frame indel, or stop codon change, or missense, or predicted deleterious by having CADD score > 15.0; or predicted to disrupt splicing by MaxEntScan; or within 2 bases into intron. In case of dominant genes, kept variants which are associated with gain of function, or hemizygous, or heterozygous, or heterozygous-amb, or compound heterozygous, or homozygous, or heterozygous-alt, or haploinsufficient and occur in at least one of the Case samples at the variant level; and not variants which are associated with gain of function, or hemizygous, or heterozygous, or heterozygous-amb, or compound heterozygous, or homozygous, or heterozygous-alt, or haploinsufficient, and occur in at least one of the control samples at the variant level in the Control samples. …”
Section: Methodsmentioning
confidence: 99%
“…Although KCNQ1, KCNH2, SCN5A, KCNJ2, CACNA1C, CALM1, CALM2, and CALM3 genes are classified as definitely causal for LQTS [32], further studies are necessary to conclude the causality of the other genes for LQTS. Notably, it is also known that a part of LQTS, SQTS, BrS, and ERS share common genetic backgrounds and that some causal genes are also associated with other cardiac phenotypes, such as atrial fibrillation (AF) [33][34][35], and/or extra-cardiac phenotypes as shown in Table 1.…”
Section: Lqtsmentioning
confidence: 99%
“…BrS (I Na ↓) [103] SEMA3A BrS (I Na ↓) [106] KCND2 ERS (I to ↑) [137], AF (I to ↑) [34]/Epilepsy (I A ↑) [147], ASD (I A ↑) [147] SLC4A3 SQTS (AE3↓) [81] KCND3…”
Section: Hey2mentioning
confidence: 99%